PENGARUH MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP SIKAP PERCAYA DIRI DAN HASIL BELAJAR SISWA SEKOLAH DASAR PADA PEMBELAJARAN BAHASA INDONESIA - Hayatun Toyibah, Hani; Sunanto, Liyana; Suhada, Dadang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Snowball Throwing learning model on students' self-confidence and learning outcomes in elementary school Indonesian language learning. This study used an experimental method with a Pretest-Posttest Control Group Design. The sample consisted of 50 fourth-grade students divided into experimental and control groups. Data collection techniques used multiple-choice tests and Likert-scale questionnaires. Data analysis used the Independent Sample t-test. The results showed a significant effect on self-confidence (Sig. 0.003 < 0.05) and learning outcomes (Sig. 0.044 < 0.05). Thus, the Snowball Throwing model effectively improves students' self-confidence and learning outcomes.